1968
DOI: 10.1037/h0025447
|View full text |Cite
|
Sign up to set email alerts
|

Personality correlates and antecedents of drinking patterns in adult males.

Abstract: Members of a longitudinal study, now in their middle 40s, were classified on the basis of their drinking patterns. The youthful and adult personality characteristics of these groups as assessed by the California Q set were compared for 3 age periods: junior high school, senior high school, and adulthood. A core of traits described the problem drinkers as undercontrolled, impulsive, and rebellious. Moderate drinkers and, especially, abstainers were overcontrolled, responsible, and able to function comfortably i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
2
2

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(119 citation statements)
references
References 23 publications
5
110
2
2
Order By: Relevance
“…For some classes of substances at least, pre-morbid characteristics could thus have a predictive value. For instance, personality traits of alcoholics have been shown to precede the onset of alcohol-related problems (Jones, 1968;Kammeier et al, 1973;Loper et al, 1973;Cloninger, 1987;Caspi et al, 1997). Parental alcohol and tobacco use were shown to be related to higher NS in offspring (Ravaja and Keltikangas-Jarvinen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For some classes of substances at least, pre-morbid characteristics could thus have a predictive value. For instance, personality traits of alcoholics have been shown to precede the onset of alcohol-related problems (Jones, 1968;Kammeier et al, 1973;Loper et al, 1973;Cloninger, 1987;Caspi et al, 1997). Parental alcohol and tobacco use were shown to be related to higher NS in offspring (Ravaja and Keltikangas-Jarvinen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal and twin studies [89][90][91][92][93][94][95][96] have consistently found antisocial behavior or conduct disorder in childhood or late adolescence to predict alcohol dependence in early adulthood. By contrast, antisocial PD did not predict incident alcohol or drug use disorders in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12 The socialization subscale of the CPI was designed to measure a constellation of personality traits that have been found to predict future alcoholism. 13 Only subjects whose scores on these tests showed them to be moderate social drinkers at low risk for alcoholism were included in the experiment. Subjects were required to abstain from food and drink for at least 4 hr prior to the experiment.…”
Section: Speech Production Talkersmentioning
confidence: 99%